Merkel Cell Carcinoma of the Left Eyelid with Metastasis to the Left Submandibular Lymph Nodes: A Case Report and Brief Review - Caroline Casey; Nina Gallo; Samuel Gallo (Case Reports in Ophthalmological Medicine)
Merkel cell carcinoma (MCC) is a cutaneous cancer often found on sun-exposed areas. MCC is rare but very often lethal making early diagnosis challenging although critical. There are only a few cases that have reported MCC of the eyelid making it often hard to identify in clinic. A 52-year-old woman with a firm nodule on the left eyelid was diagnosed with MCC that had also metastasized to a left submandibular lymph node. She underwent surgical excision of the mass and lymph node as well as parotid gland and neck dissection to rule out other metastases and then underwent radiation therapy. The aim of this study is to report a case of eyelid MCC with metastasis to a local lymph node to provide another example of the rare cancer in hopes that diagnosis and treatment options for MCC are more thoroughly studied and understood.